Artificial Neural Network Inducement for Enhancement of Cloud Computing Security - Uddin, Md. Raihan; Kabir, Kh. Mohaimenul; Arefin, Md. Taslim (2019 1st International Conference on Advances in Science, Engineering and Robotics Technology (ICASERT), 2019)
Cloud computing is a spirited topic in this epoch where IOT introducing the modern lifestyle. These embrace cost-effectiveness, time savings and the actual arrangement of computing properties. Conversely, in Cloud Computing privacy and security is a big issue where there are many kinds of thread and attack are working rapidly. In the context, the best cryptographic method AES algorithm and AI-based method ANN have chosen to work for the enhancement of the security where cloud computing demands the highest priority. In this case, this paper is proposing the highly advanced two-step security layer for cloud computing. Primarily, AES provides for the first layer security of the first stratum. In the AES algorithm, the execution is dependent on the key size of the algorithm when the number of rounds to be accomplished. A MATLAB code is developed for plaintext encryption and cipher text decryption. Experiments are conducted to measure execution times. ANN is a method of computation which is biologically stimulated. These only look like the parallel computation generated which are the basics of human learning by the biological neural network. Iris and Finger recognition is implemented using MATLAB through ANN. The paper demonstrated the great proficiency of the proposed system for the user purpose.